Gesture based implementation on neural network: Bengali sign language to text conversion - Hasan, S.M. Farzana; Rahman, Tanjina Mehnaz; Chowdhury, Anika Raisa; Biswas, Akash (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.